2005
DOI: 10.1016/j.lungcan.2004.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the promoter region of neutrophil elastase gene and lung cancer risk

Abstract: SummaryThe neutrophil elastase (NE) gene encodes a powerful serine protease that is involved in the process of normal tissue turnover, natural host defense or tissue damage in acute and chronic inflammatory disorders. Furthermore, NE was suggested as one of the determinant factors of individual susceptibility to lung cancer resulting from imbalance between α1-antitrypsin (AT) and NE. To determine whether NE plays a role in risk for lung cancer, we screened polymorphisms in the promoter region of the NE gene an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…This data are in concordance with data from the studies by Taniguchi et al and Park et al [14,15]. When our LC patients were categorized based on the predicted activity of NE, there were significantly more patients with intermediate and high NE activity, compared to those with low activity (91% vs. 9%, respectively).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This data are in concordance with data from the studies by Taniguchi et al and Park et al [14,15]. When our LC patients were categorized based on the predicted activity of NE, there were significantly more patients with intermediate and high NE activity, compared to those with low activity (91% vs. 9%, respectively).…”
Section: Discussionsupporting
confidence: 92%
“…Luciferase activity assays showed that ELA2 promoter constructs with −903T/−741G genotype had higher activity compared with the −903G/−741A construct. Based on this results, predicted activity of ELA2 genotypes are classified as: low ELA2 activity genotype (−903TG), intermediate ELA2 activity genotypes (−903TT/−741AG and −903TT/ −741AA) and high ELA2 activity genotypes (−903TT/ −741GG) [15].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that a second promoter polymorphism in the MMP‐9 gene (90(CA)14–24) affects blood MMP‐9 levels in healthy adults and obese patients . Furthermore, five polymorphisms in the NE promoter region have been linked to the risk of lung cancer . However, no relationships between the latter polymorphisms and COPD have yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In 6 out of 123 ERSD patients we found PCR (Polymerase Chain Reaction) products with two patterns of DNA fragments: 502bp/397bp and 449bp/397bp ( Figure 1 A). Sequencing of these fragments revealed two duplications in heterozygosity: an extra block composed by the 4th and 5th repetitions of the promoter region between the 5th and 6th repetitions, and an extra 52bp between the 4th and 5th repetitions, respectively (the latter was described in previous studies) [ 4 ]. In the remaining 117 patients, we identified two SNPs already described: c.-741G>A ( Figure 1 B.I–B.III) and c.-903T>G ( Figure 1 C.I,C.II).…”
Section: Resultsmentioning
confidence: 85%
“…Neutrophil elastase, a protease able to degrade several extracellular matrix proteins, is encoded by ELANE gene. Polymorphisms of ELANE gene have been associated with the development of several pathologies [ 4 , 5 , 6 ]. Indeed, the presence of mutations and single nucleotide polymorphisms (SNPs) in the codifying region and in the six repetitive tandem motifs of the promoter appear to influence the level of elastase expression, promoting proteolytic disturbances [ 5 ].…”
Section: Introductionmentioning
confidence: 99%